2016
DOI: 10.3390/s16040520
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Electronic Nose Performance Based on a Novel QPSO-KELM Model

Abstract: A novel multi-class classification method for bacteria detection termed quantum-behaved particle swarm optimization-based kernel extreme learning machine (QPSO-KELM) based on an electronic nose (E-nose) technology is proposed in this paper. Time and frequency domain features are extracted from E-nose signals used for detecting four different classes of wounds (uninfected and infected with Staphylococcu aureus, Escherichia coli and Pseudomonas aeruginosa) in this experiment. In addition, KELM is compared with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…In view of the complexity and especially the efficiency in our previous publication [38], QPSO [55,56] is leveraged to optimize the values of C in Equation (8), λ1,λ2 in Equation (12), and the model parameters of the base kernels to constitute a weighted multiple kernel and then implement the KELM shown in Equation (8), which is named QPSO-based weighted multiple kernel extreme learning machine (QWMK-ELM).…”
Section: Methodsmentioning
confidence: 99%
“…In view of the complexity and especially the efficiency in our previous publication [38], QPSO [55,56] is leveraged to optimize the values of C in Equation (8), λ1,λ2 in Equation (12), and the model parameters of the base kernels to constitute a weighted multiple kernel and then implement the KELM shown in Equation (8), which is named QPSO-based weighted multiple kernel extreme learning machine (QWMK-ELM).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, ELM's randomly generated input weights and hidden layer biases can make the algorithm unstable. Chao Peng et al [42] proposed an ELM-based Kernel Extreme Learning Machine (KELM) in combination with kernel functions for VOC detection to solve this problem. It was compared against SVM, KNN, and LDA.…”
Section: Non-linear Classification Methodsmentioning
confidence: 99%
“…Previous studies have shown that multisource information fusion can more effectively detect the composition of tea [33]. Moreover, the time domain and frequency domain features are more effective in extracting internal quality from the sensor signal array [42]. However, there are still some obstacles to the acquisition of features of cross-category tea.…”
Section: Introductionmentioning
confidence: 99%